GROWTH PRODUCTIVITY OF PAKCOY (Brassica rapa L.) AND LETTUCE (Lactuca sativa L.) PLANTS IN AQUAPONIC SYSTEMS - Emma Moko; Jenifer Nasilia Vernanda Kansil Tangkuliwutang; Helen Joan Lawalata; Livana Dethris Rawung; Johanna Zusye Wantania; Dino Rahardiyan (Universitas Veteran Bangun Nusantara, 2026)
Aquaponics is a cultivation method that integrates freshwater fish farming with hydroponics or soil-less plant cultivation, where wastewater from fish ponds is used as a source of nutrients for plants. This aquaponics system not only produces fish and fresh vegetables, but also reduces waste and water usage, making aquaponics an ideal solution for cultivation in small urban areas. This study aims to analyze and compare the growth productivity of pakcoy (Brassica rapa L.) and lettuce (Lactuca sativa L.) in an aquaponics system. This study was conducted at the Lotta Agricultural Center (SAL), Pineleng District, Minahasa Regency, North Sulawesi, from October to December 2024. The research method used a Completely Randomized Design (CRD) with two groups, namely pakcoy and lettuce plants, each with 57 replicates. The data collected included plant height, leaf width, number of leaves, biomass, and leaf chlorophyll content. The results showed that the aquaponics system had a significant effect on the growth of both types of plants. Pakcoy showed faster growth and higher productivity than lettuce, with significant differences in plant height (F = 223.160, Sig. = .000), leaf width (F =121.793, Sig. = .000), number of leaves (F = 734.323, Sig. = .000), and total biomass. Chlorophyll content in pakcoy was also higher than in lettuce, indicating greater photosynthetic capacity. The aquaponics system effectively supports the growth of pakcoy and lettuce, with pakcoy showing a better response. The aquaponics system can be an efficient sustainable agriculture solution in resource use and reducing environmental impact.